2011
DOI: 10.1021/bm2011032
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Block Copolymer Micelles with Thiol-Responsive Sheddable Coronas

Abstract: Novel sheddable micelles having hydrophilic coronas capable of being shed from biodegradable polylactide (PLA) cores by the cleavage of disulfide linkages in response to thiols were prepared by aqueous micellization of PLA-based amphiphilic block copolymers functionalized with disulfides at block junctions. These well-defined copolymers were synthesized by a combination of ring-opening polymerization and atom transfer radical polymerization in the presence of a new disulfide-functionalized double-head initiato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…50 Moreover, diverse methodologies have been used for characterization of the thermoresponsive polymeric NPs such as cryogenic transmission electron microscopy (cryo-TEM), 51 atomic force microscopy (AFM), 52 nuclear magnetic resonance (NMR) spectroscopy, 53,54 small-angle X-ray scattering (SAXS), 51,55,56 Fourier-transform infrared spectroscopy (FT-IR), 10 UV–vis, 46 and static and/or dynamic light scattering (SLS/DLS). 46,57 …”
Section: Introductionmentioning
confidence: 99%
“…50 Moreover, diverse methodologies have been used for characterization of the thermoresponsive polymeric NPs such as cryogenic transmission electron microscopy (cryo-TEM), 51 atomic force microscopy (AFM), 52 nuclear magnetic resonance (NMR) spectroscopy, 53,54 small-angle X-ray scattering (SAXS), 51,55,56 Fourier-transform infrared spectroscopy (FT-IR), 10 UV–vis, 46 and static and/or dynamic light scattering (SLS/DLS). 46,57 …”
Section: Introductionmentioning
confidence: 99%
“…The double-head agent CPADB-SS-iBuBr was synthesized by N , N ′-dicyclohexylcarbodiimide (DCC) coupling between the RAFT CTA 4-cyanopentanoic acid dithiobenzoate (CPADB) 7 and 2-hydroxyethyl-2′-(bromoisobutyryl)ethyl disulfide initiator (OH-SS-iBuBr) 8 in the presence of 4-(dimethylamino)pyridine (DMAP) as a catalyst. After purification by column chromatog-raphy, CPADB-SS-iBuBr was successfully obtained with 43.1% yield (Figure 1a).…”
mentioning
confidence: 99%
“…Chain extension using different monomers by consecutive CLRP processes always leads to block copolymers with non-degradable C-C links in the block junctions. Recently Oh et al reported the synthesis of poly(lactide)-SS-polymethacrylate amphiphilic block copolymers with SS linkages positioned at the block junction by ring-opening polymerization (ROP) and ATRP, 8 but these methods are limited to the application of cyclic monomers.…”
mentioning
confidence: 99%
“…The synthesis of HO‐ss‐Br double‐head initiator for both ROP and ATRP is described in our previous publication . In the presence of HO‐ss‐Br, a series of ROP of d,l ‐lactide (LA) mediated with tin(II) 2‐ethylhexanoate (Sn(Oct) 2 ) in toluene at 120 °C was conducted.…”
Section: Resultsmentioning
confidence: 99%